Improvement of bonding behavior of cold-rolled stainless steel/copper composite plates via surface spinel structure treatment - Bowei Wang; Baojun You; Yuting Hu; Lun Fu; Chao Yu; Hong Xiao (Journal of Materials Research and Technology)
Because the deformation coordination between stainless steel and copper is poor, it is difficult to prepare stainless steel/copper composite plates using cold roll bonding (CRB). Therefore, this study proposes a surface spinelization cold rolling process for preparing stainless steel/copper composite plates. The pre-oxidation treatment before CRB spinelized the stainless steel surface, and a solid mechanical occlusion was formed at the bonding interface after rolling. The reduction rate of the composite plates prepared via CRB was reduced, and stainless steel/copper composite plates with optimal bonding performance were obtained. The mechanical properties and microstructures of the rolled composite plates under the two surface treatment methods were compared via steel wire brush grinding and oxidation treatments on stainless steel surfaces. The results showed that the minimum reduction rate of the steel-wire brush grinding treatment was 60% and that the shear strength was 84.48 MPa. Under the surface oxidation treatment process, the two metals were bonded at a 45% reduction rate with a shear strength of 27.35 MPa. Additionally, the shear strength of the composite plates can achieve 94.82 MPa at a 60% reduction rate. The mechanism analysis shows that there are defects between the work-hardening layer and stainless-steel matrix. Moreover, the cracks generated during the rolling process are smaller, which is not conducive to the formation of mechanical occlusion. The cracks in the spinelized hardened layer prepared via the oxidation treatment were larger during rolling, and the bonding interface easily formed a strong mechanical occlusion.